Hyperglycemia, an abnormality that results from a breakdown of normal glucose control processes is also the result of molecular mechanisms to protect the insulin receptor? A hypothesis - Zerón HM; Maldonado AN; Sánchez MM (Ibom Medical Journal)
Background: Deficiency in either β-cell mass or function, or both, can lead to insufficient levels of insulin, resulting in hyperglycemia and diabetes mellitus.